Assessing flood risks and exploring opportunities for flood-based farming in the dry lowlands of Ethiopia - Desta, Gizaw; Legesse, Gizachew; Ahmed, Mohammed Irshad; Muluneh, Alemayehu; Birhanu, Belete (Frontiers in Sustainable Food Systems, 2024)
Food grown in the rainfed system in Ethiopia is frequently insufficient to meet household food needs due to recurrent drought, which causes severe food insecurity. Ethiopia's drylands have also been hit by an increase in torrential floods. As a result, the ability to adapt to shocks and risks decreases. Despite the opportunity of highland-to-lowland to lowland connectivity, the opportunities for flood-recession farming are poorly understood. This study maps flood recession opportunities incorporating national flood occurrence information, flood images, and SMAP surface soil moisture from Soil Moisture Active Passive (SMAP) images in Omo Gibe basin and Mile sub-basin. The analysis demonstrates that during the past three decades, there have been substantial flood incidents in the country's eastern, south-eastern, and southern regions. Notably, floods that